Effect of Transport Time on the Use of Reperfusion Therapy for Patients with Acute Ischemic Stroke in Korea - Choi, Jay Chol (J Korean Med Sci, 2021)
BACKGROUND: We investigated the association between geographic proximity to hospitals and the administration rate of reperfusion therapy for acute ischemic stroke. METHODS: We identified patients with acute ischemic stroke who visited the hospital within 12 hours of symptom onset from a prospective nationwide multicenter stroke registry. Reperfusion therapy was classified as intravenous thrombolysis (IVT), endovascular therapy (EVT), or combined therapy. The association between the proportion of patients who were treated with reperfusion therapy and the ground transport time was evaluated using a spline regression analysis adjusted for patient-level characteristics. We also estimated the proportion of Korean population that lived within each 30-minute incremental service area from 67 stroke centers accredited by the Korean Stroke Society. RESULTS: Of 12,172 patients (mean age, 68 ± 13 years; men, 59.7%) who met the eligibility criteria, 96.5% lived within 90 minutes of ground transport time from the admitting hospital. The proportion of patients treated with IVT decreased significantly when stroke patients lived beyond 90 minutes of the transport time (P = 0.006). The proportion treated with EVT also showed a similar trend with the transport time. Based on the residential area, 98.4% of Korean population was accessible to 67 stroke centers within 90 minutes. CONCLUSION: The use of reperfusion therapy for acute stroke decreased when patients lived beyond 90 minutes of the ground transport time from the hospital. More than 95% of the South Korean population was accessible to 67 stroke centers within 90 minutes of the ground transport time.